Can Altruism Lead to a Willingness to Take Risks? - Oded Stark (Institute of Labor Economics (IZA), 2023)
I study attitudes towards risk taking in cases where a person relates to others positively, namely altruistically. This study is needed because it is unclear how altruism influences the inclination of an altruistic person to take risks. Will this person's risk-taking behavior differ if the utility of another person does not enter his utility function? Does being altruistic cause a person to become more reluctant to take risks because a risky undertaking turning sour will also damage his ability to make altruistic transfers? Or does altruism induce a person to resort to risky behavior because the reward for a successful outcome is amplified by the outcome facilitating a bigger transfer to the beneficiary of the altruistic act? Specifically, holding constant other variables, I ask: is an altruistic person more risk averse or less risk averse than a comparable person who is not altruistic? In response to this question, using a simple model in which preferences are represented by a logarithmic utility function, I show that an altruistic person who is an active donor (benefactor) is less risk averse than a comparable person who is not altruistic: altruism is a cause of greater willingness to take risks. The finding that the altruism trait causes greater willingness to take risks has not previously been noted in the existing literature.
Keywords: D01; D64; D81; G41; 330; altruism; altruistic transfers; relative risk aversion; intensity of altruism